2022
DOI: 10.3390/life12122057
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Vaccination against SARS-CoV-2 on Long COVID-19: A Narrative Review

Abstract: Vaccines against SARS-CoV-2 have saved millions of lives and played an important role in containing the COVID-19 pandemic. Vaccination against SARS-CoV-2 is also associated with reduced disease severity and, perhaps, with COVID-19 symptom burden. In this narrative review, we present, in a clinically relevant question-and-answer manner, the evidence regarding the association between vaccination against SARS-CoV-2 and long COVID-19. We discuss how the mechanism of action of vaccines could interplay with the path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 79 publications
0
14
0
Order By: Relevance
“…On the other hand, previous evidence (e.g., [ 20 ]) concluded from six articles that vaccination could reduce the risk of post-/long-COVID, suggesting that every additional dose is more effective (see also [ 41 , 42 ]) in reducing the risk for post-/long-COVID. Overall, there is an agreement [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ] that vaccination cannot entirely avoid the risk of breakthrough infections and, thus, long-term symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, previous evidence (e.g., [ 20 ]) concluded from six articles that vaccination could reduce the risk of post-/long-COVID, suggesting that every additional dose is more effective (see also [ 41 , 42 ]) in reducing the risk for post-/long-COVID. Overall, there is an agreement [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ] that vaccination cannot entirely avoid the risk of breakthrough infections and, thus, long-term symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…An important strategy to manage the impact of acute infections and prevent the long-term effects of COVID-19 in the first place is vaccinations. Some previous research on SARS-CoV-2 has shown that vaccinations can help to reduce infection severity or prevent severe symptom developments over time [ 19 ]. This can also lower the risk of hospitalization and death.…”
Section: Introductionmentioning
confidence: 99%
“…The COVID-19 vaccines work by triggering an immune response against the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) virus [ 21 , 22 ]. The vaccines can either deliver viral components, such as viral proteins, or genetic material delivered by a vector, such as a benign virus.…”
Section: Anti-covid Vaccination: Mechanisms Of Actionmentioning
confidence: 99%
“…These findings were supported by 3 different in-depth assessments of the UK survey and several smaller studies investigating the therapeutic effect of vaccination in long COVID. 5–7…”
mentioning
confidence: 99%
“…These findings were supported by 3 different in-depth assessments of the UK survey and several smaller studies investigating the therapeutic effect of vaccination in long COVID. [5][6][7] Therapeutic vaccinations have a long history. In 1891, Robert Koch promoted the use of tuberculin as a specific treatment for pulmonary tuberculosis, with generally disappointing results and substantial "reactions."…”
mentioning
confidence: 99%